2019
DOI: 10.17239/l1esll-2019.19.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Dutch teachers' beliefs on linguistic concepts and reflective judgement in grammar teaching

Abstract: Teacher beliefs have been shown to play a major role in shaping educational practice, especially in the area of grammar teaching-an area of language education that teachers have particularly strong views on. Traditional grammar education is regularly criticized for its focus on rules-of-thumb rather than on insights from modern linguistics, and for its focus on lower order thinking. A growing body of literature on grammar teaching promotes the opposite, arguing for more linguistic conceptual knowledge and refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
3
0
2
Order By: Relevance
“…While Dutch teachers appear to be open towards a type of grammar teaching that values grammatical understanding in itself (i.e., metaconceptual lessons, cf. Van Rijt et al, 2020b), their own grammatical knowledge of such metaconcepts appears to be lacking (Van Rijt et al, 2019c, which is a shortcoming that is documented across different educational settings (e.g., Alderson & Hudson, 2013;Sangster et al, 2013). It seems fair to assume that limitations in subject knowledge can influence the way in which teachers think about and justify a topic such as grammar education.…”
Section: Discussionmentioning
confidence: 99%
“…While Dutch teachers appear to be open towards a type of grammar teaching that values grammatical understanding in itself (i.e., metaconceptual lessons, cf. Van Rijt et al, 2020b), their own grammatical knowledge of such metaconcepts appears to be lacking (Van Rijt et al, 2019c, which is a shortcoming that is documented across different educational settings (e.g., Alderson & Hudson, 2013;Sangster et al, 2013). It seems fair to assume that limitations in subject knowledge can influence the way in which teachers think about and justify a topic such as grammar education.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, there are strong indications that currently, traditional grammar teaching is still dominant in the Netherlands (Tol-Verkuyl 2001;Bonset and Hoogeveen 2010;Van Gelderen 2010;Van Rijt. et al 2019c).…”
Section: Dutch Contextmentioning
confidence: 99%
“…Meyer and Land (2005) described these complicated but elementary concepts as "troublesome," and suggested that in literary studies, irony might be an example of such troublesome concepts (see also Corrigan, 2019;Johansson, 2019). While research on learning L1 concepts and determining how to use them has become more significant recently when concerning grammatical concepts (e.g., Camps & Fontich, 2019;Myhill, 2018;Štěpáník, 2019;van Rijt et al, 2019), there are considerably fewer studies on how students learn and understand concepts that are central in literature education. However, research has demonstrated how students enhance their interpretation and reading of literary texts with the assistance of suitable concepts (e.g., Doecke & van de Ven 2012;Wolfe 2004).…”
Section: Learning Literary Concepts and Classroom Interactionmentioning
confidence: 99%